Pengaruh Brand Ambassador, Brand Personality Dan Korean Wave Terhadap Keputusan Pembelian Produk Nature Republik Aloe Vera - Safirotul Mu’nisah; Muhammad Ridwan Basalamah; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of entrepreneurship education, resilience and motivation on interest in entrepreneurship. The object of this research is students of the Faculty of Economics and Business, Islamic University of Malang with a total sample of 81 students. The sampling technique used purposive sampling. Data collection techniques using questionnaires and data analysis tools. Based on the results of a partial research analysis, brand ambassador has a significant effect on buying decision. While partially brand ambassador has a significant effect on buying decision. Meanwhile, partially korean wave has a significant effect on buying decision. Keywords: Brand Ambassador, Brand Personality, Korean Wave and Buying Decision